The Influence of the Implementation of Personnel Management Information System, Utilization of Information Technology and Human Resource Competence on the Management of Personnel Administration - Arief Hadianto; Ali Purnomo (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2021)
SIMPEG is very important in the management of personnel administration considering that employees are an important asset in organizing the organization. This research was conducted by a questionnaire survey method that was distributed to 64 respondents who were employees of the First-Class Immigration Office of Tanjung Priok. The number of samples in this study as many as 64 people with sampling technique used is the total sampling. The analysis used in this research is correlation and regression, t test, F test and coefficient of determination test. The result of research proves that the implementation of SIMPEG, the utilization of information technology and human resource competency, either partially or simultaneously, has a positive and significant influence on the management of personnel administration at the First-Class Immigration Office Tanjung Priok. The number of samples in this study as many as 64 people with sampling technique used is the total sampling. The result of research proves that the implementation of SIMPEG, the utilization of information technology and human resource competency, either partially or simultaneously, has a positive and significant influence on the management of personnel administration at the First-Class Immigration Office Tanjung Priok. The number of samples in this study as many as 64 people with sampling technique used is the total sampling. The analysis used in this research is correlation and regression, t test, F test and coefficient of determination test. The result of research proves that the implementation of SIMPEG, the utilization of information technology and human resource competency, either partially or simultaneously, has a positive and significant influence on the management of personnel administration at the First-Class Immigration Office Tanjung Priok.